Purple phototrophic bacterium enhances stevioside yield by Stevia rebaudiana Bertoni via foliar spray and rhizosphere irrigation. - Jing Wu; Yiming Wang; Xiangui Lin (PLoS ONE)
This study was conducted to compare the effects of foliar spray and rhizosphere irrigation with purple phototrophic bacteria (PPB) on growth and stevioside (ST) yield of Stevia. rebaudiana. The S. rebaudiana plants were treated by foliar spray, rhizosphere irrigation, and spray plus irrigation with PPB for 10 days, respectively. All treatments enhanced growth of S. rebaudiana, and the foliar method was more efficient than irrigation. Spraying combined with irrigation increased the ST yield plant (-1) by 69.2% as compared to the control. The soil dehydrogenase activity, S. rebaudiana shoot biomass, chlorophyll content in new leaves, and soluble sugar in old leaves were affected significantly by S+I treatment, too. The PPB probably works in the rhizosphere by activating the metabolic activity of soil bacteria, and on leaves by excreting phytohormones or enhancing the activity of phyllosphere microorganisms.